Total phenolics, antioxidant, and physical properties of red chili peppers (Capsicum annum L.) as affected by drying methods - Natoavina T. Faliarizao; Muhammad Siddiq; Kirk D. Dolan (International Journal of Food Properties)
Chili pepper (Capsicum annuum) is a popular spice, and its use has increased significantly in recent years, particularly in Western countries. Our objectives were to evaluate the effect of hot-air (60°C), vacuum, infra-red, and freeze-drying on the quality of dried chilies. Physico-chemical properties evaluated were total phenolic content (TPC), antioxidant properties (ABTS+, FRAP, DPPH), instrumental color (L*, a*, and b* values), total color difference (ΔE), browning-index (BI), bulk-density, and texture. The TPC values of dried chilies varied from 498.40 to 528.07 mg GAE/g, db. The DPPH and ABTS+ values (µmol TE/g, db) ranged between 184.00 (infra-red) to 195.56 (hot-air) and 167.13 (freeze) to 181.30 (vacuum), respectively, with no significant differences across drying methods (p > 0.05). Freeze- and vacuum-drying retained significantly higher (p < 0.05) FRAP values (155–158 µmol TE/g db) than hot-air or infra-red drying. There were no differences in Hunter color L* and b* values, however, vacuum- and freeze-drying retained higher color a* values (44.38–44.48) than hot-air dried sample (36.59). The ΔE and American Spice Trade Association (ASTA) values were not different across drying methods (p >0 .05), whereas the BI values were lower in freeze-dried chilies. These findings highlighted the importance of optimizing drying techniques to maintain the quality and marketability of chili peppers.